Hubungan Paparan Pestisida Dengan Kadar HB (Hemoglobin) pada Petani Penyemprot Pestisida di Desa Sumberejo Kecamatan Ngablak Magelang (PESTICIDE EXPOSURE RELATIONSHIP WITH HB (HEMOGLOBIN) CONTAINS TO FARMERS PESTICIDES IN SUMBEREJO DESA DISTRICT NGABLAK M - Fianti andua; Onny Setiani; Hanan Lanang Dangiran; Tri Joko (Jurnal Kesehatan Masyarakat (Undip), 2017)
Pesticide chemical are chemical compounds that are toxic, which is used to eradicate plant pests or weeds. The impact of pesticides can be on farmers sprayers, families and neighbors. The purpose of this study was to know the exposure of pesticides and hemoglobin (HB) to pesticide spraying farmers in the village of Sumberejo Ngablak District Magelang. Sampel as many as 43 farmers with cross sectional with purposive sampling method. The results showed the relation between the completeness of APD (p = 1,000), spraying frequency (p = 1,000), spraying time (p = 0,029), pesticide type (0,515), kholinesterase (p = 0,421) with Hb. This research has no relationship of exposure of pesticide with Hb level in Sumberejo village, Ngablak Magelang sub-district.